A grammar of the Luwian language - Yakubovich, Ilya. (Wiesbaden)
xx, 346 sayfa
Keywords: “Luwian is a language of Pre-Classical Anatolia and Syria, which is attested in writing between 1500 and 700 BC. It belongs to the Anatolian group of the Indo-European languages and thus represents a close relative of Hittite. It is attested in two scripts: Anatolian hieroglyphs and Mesopotamian cuneiform. Ilya Yakubovich and Elisabeth Rieken present the first comprehensive grammar of the Luwian language that is based on the study of both cuneiform and hieroglyphic text corpora. It comprises the synchronic description of Luwian phonology, morphology and syntax and is written in a language that is also understandable to non-linguists. The grammar is based on original research, and many of its aspects go beyond the state of knowledge reflected in earlier scientific works. It can be recommended as a reference tool within the context of teaching and studying Luwian in a university setting and at the same time be used for self-study of Luwian in combination with the published text editions.“ --